A comparative study of high and low molecular weight microtubule-associated protein 2 (HMW-MAP2 and MAP2c) in differentiating neurons and transfected fibroblasts cells. - Echeverri, Christophe de Jesus. (University of Ottawa (Canada), 1993)
Microtubule-associated protein 2 (MAP2) is the most abundant MAP in vertebrate brain tissues, and the best studied of all structural MAPs. In adult brain, it is present as one or two high-molecular weight polypeptides (HMW-MAP2, $\sim$280kDa by SDS-PAGE) which segregate to the somato-dendritic compartments of neurons. Apart from its ontogeny and sequence, little is known about MAP2c biochemistry, although sequence similarities with HMW-MAP2 suggest that the smaller isoform should also bind to MTs, promote their assembly, stabilize them, and possibly induce bundling. This thesis aimed to examine these questions about MAP2c by studying it in parallel with HMW-MAP2 both in differentiating neurons, and in transfected fibroblasts. Neuronal differentiation was examined in retinoic acid-induced P19 embryonal carcinoma cells, using an anti-$\beta$III-tubulin antibody to identify neurons. Expression of MAP2 was examined using three monoclonal antibodies, two of which (HM2 and AP18) recognized all forms of MAP2, while the third (AP14) was specific for HMW-MAP2. Onset of detectable expression of MAP2 was found to coincide with initial neurite outgrowth of P19 EC-derived neurons. The HM2 antibody stained almost all visible neurons, while AP18 stained a smaller subset, and AP14, the smallest. Only the HM2 antibody stained filopodia on some cell bodies and neurite shafts, as well as some growth cones. It is proposed that MAP2 is present as two or more subpopulations which sort differently within the cell. Transient transfections into 3T3 fibroblasts confirmed that MAP2c binds to MTs, stabilizes them against colchicine-induced depolymerization, and induces the formation of MT bundles. It is proposed that MAP2-induced bundles initially arise through the funnelling of MTOC-based MTs into thin cytoplasmic extensions which are eventually resorbed into the cell body. MT bundles are then released from the MTOC, and their stability is slightly decreased as a result. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.